1995
DOI: 10.1071/bt9950451
|View full text |Cite
|
Sign up to set email alerts
|

Protogyny, Self-Incompatibility and Pollination in Anthocercis gracilis (Solanaceae)

Abstract: The pollination biology of A. gracilis was examined in glasshouse plants and natural populations. The species is both protogynous and pre-zygotically self-sterile (self-incompatible). Protogyny prevents autopollination (autogamous self-pollination), and self-incompatibility avoids geitonogamous self-fertilisation. This sequence is essential because prior selfing blocks the style with pollen tubes and prevents subsequent outcrossing. Flowers have no discernible daytime odour, the pollen is clumped and not easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As this study only assessed self-compatibility to the stage of pollen tube penetration of the ovule, we cannot discount later-acting prezygotic control of the breeding system in E. argutifolia, as has been recorded in species from other plant families ( e.g. Kenrick & Knox, 1985;Stace, 1995). It should be noted, however, that studies investigating early seed development in Eucalyptus have found no evidence of self-incompatibility operating between the stages of pollen tube penetration of the ovule and fertilization (Sedgley, 1989;.…”
Section: Discussionmentioning
confidence: 99%
“…As this study only assessed self-compatibility to the stage of pollen tube penetration of the ovule, we cannot discount later-acting prezygotic control of the breeding system in E. argutifolia, as has been recorded in species from other plant families ( e.g. Kenrick & Knox, 1985;Stace, 1995). It should be noted, however, that studies investigating early seed development in Eucalyptus have found no evidence of self-incompatibility operating between the stages of pollen tube penetration of the ovule and fertilization (Sedgley, 1989;.…”
Section: Discussionmentioning
confidence: 99%
“…Other taxa have received less research attention (e.g. Stace 1995;Monks 1999;Close et al 2006;Nield et al 2009), with some threatened species, such as Tetraria australiensis C.B. Clarke (a perennial, tufted sedge) having no published biological information.…”
Section: Floristics and Weedsmentioning
confidence: 99%